2011
DOI: 10.1128/jcm.01817-10
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Group 1 Trypanosoma brucei gambiense by Loop-Mediated Isothermal Amplification

Abstract: Trypanosoma brucei gambiense group 1 is the major causative agent of the Gambian human African trypanosomiasis (HAT). Accurate diagnosis of Gambian HAT is still challenged by lack of precise diagnostic methods, low and fluctuating parasitemia, and generally poor services in the areas of endemicity. In this study, we designed a rapid loop-mediated isothermal amplification (LAMP) test for T. b. gambiense based on the 3 end of the T. b. gambiense-specific glycoprotein (TgsGP) gene. The test is specific and amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 42 publications
0
34
0
3
Order By: Relevance
“…More promising is the ability of the LAMP method to overcome potential inhibitors in crude sand fly templates, an issue of particular concern for PCR assays, and still not compromise its detection sensitivity down to levels of 0.1 and 0.01 parasites. It is suggested that a significant amount of parasite DNA is lost during the extraction process, resulting in a lower detection limit when purified DNA is used as a template (Njiru et al, 2011). Other studies have shown superior tolerance of LAMP tests for biological substances (Kaneko et al, 2007;Poon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…More promising is the ability of the LAMP method to overcome potential inhibitors in crude sand fly templates, an issue of particular concern for PCR assays, and still not compromise its detection sensitivity down to levels of 0.1 and 0.01 parasites. It is suggested that a significant amount of parasite DNA is lost during the extraction process, resulting in a lower detection limit when purified DNA is used as a template (Njiru et al, 2011). Other studies have shown superior tolerance of LAMP tests for biological substances (Kaneko et al, 2007;Poon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One approach for simplifying testing has been to incorporate an oligochromatographic dipstick device for amplicon detection after conventional PCR (Deborggraeve et al, 2006). However, amplification can be further simplified through use of isothermal amplification methods such as LAMP (Kuboki et al, 2003;Njiru, Mikosza, Armstrong, et al, 2008;Njiru, Mikosza, Matovu, et al, 2008;Njiru, Traub, Ouma, Enyaru, & Matovu, 2011) and NASBA (Matovu et al, 2010;Mugasa et al, 2009). These isothermal techniques have demonstrated high analytical sensitivity and specificity, comparable or superior to PCR.…”
Section: Diagnostic Modalitiesmentioning
confidence: 98%
“…gambiense-and T.b. rhodesiense-specific LAMP assays have been developed by Njiru et al [41,45]. LAMP targeting the SRA gene for diagnosis of rhodesiense sleeping sickness showed a detection limit of one trypanosome per ml blood using heat-treated buffy coat, which is 1000-fold more sensitive than conventional SRA PCR [45].…”
Section: Dna Detection Platformsmentioning
confidence: 99%
“…A similar low detection level was reached for the T.b. gambiense LAMP using the TgsGP gene [41]. LAMP product visualization with hydroxynaphtol blue was scored favorable over turbidimetry and colorimetry with Quant-iT™ PicoGreen ® and calcein-MnCl 2 in a comparative study performed in 2010 [50].…”
Section: Dna Detection Platformsmentioning
confidence: 99%